2009
DOI: 10.1074/jbc.m109.018077
|View full text |Cite
|
Sign up to set email alerts
|

NMR Conformational and Dynamic Consequences of a Gly to Ser Substitution in an Osteogenesis Imperfecta Collagen Model Peptide

Abstract: Close packing of three chains in a standard collagen triple helix requires Gly as every third residue. Missense mutations replacing one Gly by a larger residue in the tripeptide repeating sequence in type I collagen are common molecular causes of osteogenesis imperfecta. The structural and dynamic consequences of such mutations are addressed here by NMR studies on a peptide with a Gly-to-Ser substitution within an ␣1(I) sequence. Distances derived from nuclear Overhauser effects indicate that the three Ser res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(68 citation statements)
references
References 34 publications
5
63
0
Order By: Relevance
“…Despite the perturbations in hydrogen bonding, J-coupling values indicate the dihedral angles for the Ala16 residues did not vary significantly from those expected for a standard triple-helix. A previous study on a Gly to Ala substitution within a (Pro-Hyp-Gly) 10 peptide showed one of the three Ala residues had a J-coupling of 8.6 Hz, which is not compatible with a triple-helix structure [18], while all three Ala seem to be able to participate in a triple-helix structure in the current KAD context. Both Ala and Gly were found to be rigid on picoseconds time scale, suggesting any perturbations are occurring on a much longer time scale.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Despite the perturbations in hydrogen bonding, J-coupling values indicate the dihedral angles for the Ala16 residues did not vary significantly from those expected for a standard triple-helix. A previous study on a Gly to Ala substitution within a (Pro-Hyp-Gly) 10 peptide showed one of the three Ala residues had a J-coupling of 8.6 Hz, which is not compatible with a triple-helix structure [18], while all three Ala seem to be able to participate in a triple-helix structure in the current KAD context. Both Ala and Gly were found to be rigid on picoseconds time scale, suggesting any perturbations are occurring on a much longer time scale.…”
Section: Discussionmentioning
confidence: 85%
“…A value greater than −4.6 ppb/°C supports the presence of a hydrogen bond [23, 18]. The monomer resonances of Gly7 and Gly16 in peptide T1-655 and T1-655[G16A] at pH 7 show much more negative values than this cut-off value, indicating the absence of hydrogen-bonding (Figure 5B).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Residues in the triple helical conformation typically contain phi angles from Ϫ55 to Ϫ75 degrees and have a corresponding J coupling value of 4 -6 Hz (36,39,60 Dynamics of the Model Peptides-Hydrogen exchange experiments were performed on the five model peptides at all the labeled positions to explore the protection of amide protons from solvent (supplemental Table S1). Residue-specific local stabilities were calculated from the protection factors as described under "Experimental Procedures" (Fig.…”
Section: Nmr Studies On Peptides Modeling the Collagenase Cleavage Simentioning
confidence: 99%
“…NMR studies on peptide models of collagen are powerful approaches for probing the conformation and dynamics of individual chains of the triple helix directly at the specific residue level (35)(36)(37)(38)(39). Here we use NMR to characterize the differences in conformation and dynamics at the natural GlyϳIle-Ala cleavage site versus potential cleavage sites.…”
mentioning
confidence: 99%